Image analysis and recognition 5th International Conference, ICIAR 2008, Póvoa de Varzim, Portugal, June 25-27, 2008 : proceedings - ICIAR 2008 (Lecture notes in computer science ;)
This book constitutes the refereed proceedings of the 5th International Conference on Image Analysis and Recognition, ICIAR 2008, held in Póvoa do Varzim, Portugal, in June 2008. The 110 revised full papers presented together with 2 invited papers were carefully reviewed and selected from 226 submissions. The papers are organized in topical sections on image restoration and enhancement, image and video segmentation, non-linear image processing, image and video coding and encryption, indexing and retrieval, computer vision, feature extraction and classification, shape representation and matching, object recognition, character recognition, texture and motion analysis, tracking, biomedical image analysis, biometrics, face recognition, and a special session on recent advances in multimodal biometric systems and applications. . Invited papers -- Image restoration and enhancement -- Image and video segmentation -- Non-linear image processing -- Image and video coding and encryption -- Indexing and retrieval -- Computer vision -- Feature extraction and classification -- Shape representation and matching -- Object recognition -- Character recognition -- Texture and motion analysis -- Tracking -- Biomedical image analysis -- Biometrics -- Face recognition -- Special session: recent advances in multimodal biometric systems -- Applications.